Analysis of IoT Technology Utilization and Inventory Management System on Operational Efficiency and Visitor Experience at Tourism Destinations in Bandung - Judijanto, Loso; Suharto, Bambang; Amrullah, Ata (Westscience Press, 2024)
This study examines the impact of IoT technology utilization and inventory management systems on operational efficiency and visitor experience at tourism destinations in Bandung City. Employing a quantitative research approach, data were collected from 220 respondents using a structured questionnaire with a Likert scale (1–5). The relationships among variables were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that both IoT technology and inventory management systems significantly enhance operational efficiency, which in turn positively impacts visitor experience. IoT technology showed a stronger direct effect on visitor experience, while inventory management systems had a greater influence on operational efficiency. Operational efficiency also played a mediating role, linking technological and management practices to improved visitor satisfaction. These results highlight the importance of integrating advanced technologies and efficient management systems to enhance the competitiveness and service quality of tourism destinations. The study provides actionable insights for tourism stakeholders to prioritize technology investments and strategic planning for sustainable growth.